Exploring clinical and gene expression markers of benefit from FOLFOXIRI/bevacizumab in patients with BRAF-mutated metastatic colorectal cancer: Subgroup analyses of the TRIBE2 study. (August 2021) - Moretto, Roberto; Giordano, Mirella; Poma, Anello M.; Passardi, Alessandro; Boccaccino, Alessandra; Pietrantonio, Filippo; Tomasello, Gianluca; Aprile, Giuseppe; Lonardi, Sara; Conca, Veronica; Granetto, Cristina; Frassoldati, Antonio; et al.
Abstract: Background: Recent data from the TRIBE2 study have failed to suggest a higher magnitude of benefit from upfront FOLFOXIRI/bevacizumab in patients with BRAF -mutant metastatic colorectal cancer (mCRC) as previously reported in the TRIBE study. Patients and methods: Clinical characteristics and gene expression signatures of patients with BRAF-mutant mCRC enrolled in the TRIBE2 study were evaluated with the aim of understanding that patients may derive benefit from the intensification of the upfront chemotherapy. Results: Of 46 BRAF-mutant tumour samples analysed, 24 (52%) and 22 (48%) were classified as BM1 and BM2, respectively, and 27 (59%) and 19 (41%) were assigned to ligand-independent (LI) and ligand-dependent (LD) Wnt pathway subgroups, respectively. No prognostic impact was shown for both BM1/BM2 and LI/LD subtypes. No interaction was evident between BM1/BM2 or LI/LD signatures and the benefit provided by FOLFOXIRI/bevacizumab. Significant interaction effect was evident in terms of progression-free survival between treatment arm and primary tumour sidedness ( P = 0.05) and Eastern Cooperative Oncology Group performance status (ECOG-PS; P < 0.001). Conclusions: Gene expression analysis failed to identify patients with BRAF-mutant mCRC candidate to upfront FOLFOXIRI/bevacizumab. ECOG-PS >0 and left-sidedness seem associated with no benefit from the intensified treatment. Highlights: A restricted panel of 44 genes discerns BM1/BM2 subtypes of BRAF mut mCRC. AXIN2 expression distinguishes LI versus LD Wnt pathway activation of BRAF mut mCRC. No prognostic impact was shown for both BM1/BM2 and LI/LD subtypes. No predictive effect of both BM1/BM2 and LI/LD subtypes was shown for FOLFOXIRI/bev. ECOG-PS >0 and left-sidedness seem associated with no benefit from FOLFOXIRI/bev.